Non-invasive cardiac activation mapping and identification of severity of epicardial substrate in Brugada Syndrome: a case report - Iacopino, Saverio; Sorrenti, Paolo; Campagna, Giuseppe; Fabiano, Gennaro; Fabiano, Emmanuel; Colella, Jacopo (Frontiers in Cardiovascular Medicine, 2024)
Introduction It has recently been shown that electrocardiographic imaging (ECGi) can be employed in individuals undergoing an ajmaline test who have Brugada Syndrome (BrS), to evaluate the extent of substrate-involved arrhythmia in the right ventricular overflow tract (RVOT). For the first time, we stratify the risk of sudden cardiac death (SCD) in BrS during ajmaline testing using the dST-Tiso interval (a robust predictor of the inducibility of ventricular arrhythmias (VAs) in the presence of drug-induced BrS type-1 pattern) in combination with ECGi technology. Case presentation We studied a 48-year-old man with BrS ECG type-2 pattern and presence of J-wave without a family history of SCD but with a previous syncope. Transthoracic echocardiography and cardiac magnetic resonance imaging were performed, showing normal results. The ECG was performed to assess the novel ECG marker “dST-Tiso interval.” The 3D epicardial mapping of the RVOT surface was performed with the support of a non-contact cardiac mapping system in sinus rhythm during ajmaline infusion. The examination of the propagation map unveiled the presence of multiple conduction blocks in this pathologic epicardial region, and the conduction blocks were identified within the central part and/or near the boundary separating the normal and slow conduction areas. Conclusion The dST-Tiso interval, which lies between the onset and termination of the coved ST-segment elevation and serves as a robust predictor of VA inducibility in cases of drug-induced BrS type-1 pattern, was utilized in conjunction with ECGi technology (employed for the non-invasive confirmation and identification of the pathological substrate area). This combined approach was applied to stratify the risk of SCD in BrS during ajmaline testing, alongside clinical scores.